REFORMASI BIROKRASI DAN INOVASI PEMBERDAYAAN MASYARAKAT - Marzuki Marzuki (Jurnal Ilmu Pemerintahan Widya Praja, 2016)
AbstractReform of the bureaucracy associated with the effort to create innovation. In the context of governance, innovation is a revision of the current system and are still in the corridor structurelongterm planning. The most important thing in the governance of innovation is always thenew things both large and small in the daily bureaucratic practice, so that innovation becomes‘routine’ in the new bureaucracy. One role of government is to empower the community. Alongwith the birth of bureaucratic reform policy, it is expected that the innovation will be born incommunity empowerment. The research problem is the role of government in the innovationcommunity empowerment in the reform era bureaucracy today. While the purpose of this study wasto determine the role of government in the innovation community empowerment in line with thepolicy of bureaucratic reform. The results showed that community empowerment in the reform erabureaucracy wanted the role of government as advisors, improve the role of professional servicesinto community service. The role of government in that context is the reduction of barriers andobstacles to creativity and participation, increased access to services to support various socialand economic activities of society, and develop programs to further enhance the capabilities andallowing the public play an active role in harnessing and utilizing productive resources provided soas to have a high added value in order to improve the welfare of society.